Daily parathyroid hormone administration enhances bone turnover and preserves bone structure after severe immobilization‐induced bone loss. Issue 18 (28th September 2017) - Harlow, Lauren; Sahbani, Karim; Nyman, Jeffry S.; Cardozo, Christopher P.; Bauman, William A.; Tawfeek, Hesham A.
Abstract: Immobilization, as a result of motor‐complete spinal cord injury (SCI), is associated with severe osteoporosis. Whether parathyroid hormone (PTH) administration would reduce bone loss after SCI remains unclear. Thus, female mice underwent sham or surgery to produce complete spinal cord transection. PTH (80 μ g/kg) or vehicle was injected subcutaneously (SC) daily starting on the day of surgery and continued for 35 days. Isolated tibias and femurs were examined by microcomputed tomography scanning (micro‐CT) and histology and serum markers of bone turnover were measured. Micro‐CT analysis of tibial metaphysis revealed that the SCI‐vehicle animals exhibited 49% reduction in fractional trabecular bone volume and 18% in trabecular thickness compared to sham‐vehicle controls. SCI‐vehicle animals also had 15% lower femoral cortical thickness and 16% higher cortical porosity than sham‐vehicle counterparts. Interestingly, PTH administration to SCI animals restored 78% of bone volume, increased connectivity to 366%, and lowered structure model index by 10% compared to sham‐vehicle animals. PTH further favorably attenuated femoral cortical bone loss to 5% and prevented the SCI‐associated cortical porosity. Histomorphometry evaluation of femurs of SCI‐vehicle animals demonstrated a marked 49% and 38% decline in osteoblast and osteoclast number, respectively, and 35% reduction in bone formation rate. In contrast, SCI‐PTH animals showed preserved osteoblast and osteoclast numbers and enhanced bone formation rate. Furthermore, SCI‐PTH animals had higher levels of bone formation and resorption markers than either SCI‐ or sham‐vehicle groups. Collectively, these findings suggest that intermittent PTH receptor activation is an effective therapeutic strategy to preserve bone integrity after severe immobilization. Abstract : Spinal cord injury (SCI) causes severe bone loss that is resistant to antiresorptive agents. We show for the first time that daily PTH administration prevents SCI‐induced bone loss by promoting bone turnover, thus improving bone structure. The study has significant therapeutic implications for immobilization‐induced osteoporosis.